Vitamin A and Bone Health: A Review on Current Evidence - Michelle Min Fang Yee; Kok-Yong Chin; Soelaiman Ima-Nirwana; Sok Kuan Wong (Molecules, 2021)
Vitamin A is a fat-soluble micronutrient essential for growth, immunity, and good vision. The preformed retinol is commonly found in food of animal origin whereas provitamin A is derived from food of plant origin. This review summarises the current evidence from animal, human and cell-culture studies on the effects of vitamin A towards bone health. Animal studies showed that the negative effects of retinol on the skeleton were observed at higher concentrations, especially on the cortical bone. In humans, the direct relationship between vitamin A and poor bone health was more pronounced in individuals with obesity or vitamin D deficiency. Mechanistically, vitamin A differentially influenced the stages of osteogenesis by enhancing early osteoblastic differentiation and inhibiting bone mineralisation via retinoic acid receptor (RAR) signalling and modulation of osteocyte/osteoblast-related bone peptides. However, adequate vitamin A intake through food or supplements was shown to maintain healthy bones. Meanwhile, provitamin A (carotene and β-cryptoxanthin) may also protect bone. In vitro evidence showed that carotene and β-cryptoxanthin may serve as precursors for retinoids, specifically all-trans-retinoic acid, which serve as ligand for RARs to promote osteogenesis and suppressed nuclear factor-kappa B activation to inhibit the differentiation and maturation of osteoclasts. In conclusion, we suggest that both vitamin A and provitamin A may be potential bone-protecting agents, and more studies are warranted to support this hypothesis.